Features of the distribution of Islam in Central Asia (on the example of Uzbekistan) (Eurasian Journal of Religious Studies, 2022)
During the years of independence, research on the problems of Islam and Islamic culture has intensified in Uzbekistan. Large-scale work is being carried out to preserve and develop the national spiritual culture, values, and traditions. And the purpose of this article is to study the spread of Islam in the Central Asian region, in particular in Uzbekistan. The processes that took place on the Arabian Peninsula, which led to the emergence of Islam and the creation of a huge theocratic state - the Arab Caliphate, which began to conquer the Central Asian states from the second half of the 7th century, are analyzed. Four stages of the aggressive policy are revealed, differing in duration, goals and results. Four stages of the aggressive policy are revealed, differing in duration, goals and results. It is noted that the Arab Caliphate viewed the conquest of Maverannahr as one of the richest sources of its income. Although the prophet Muhammad officially undertook these campaigns to neighboring countries with the ideological goal of spreading Islam. The reasons for the victories of the Arabs over the local population are analyzed. The author sees the main reason not only in the strength of the Arabs, but also in the fact that the occupied countries were distinguished by political, social, cultural fragmentation, the presence of acute economic problems. Central Asia was divided into many small states and was not able to provide a tough, serious rebuff to the Arabs. The conquest of Central Asia by the Arabs, which lasted almost a hundred years, ended in the 1930s and 1940s. 8th centuryThe Arabs behaved like conquerors - they robbed, took away decent dwellings, evicted their owners from their homes, robbed artisans, destroyed irrigation systems, as a result of which the lands turned into deserts. These actions and the brutal forms of exploitation of the population by the Arabs led to uprisings. The uprising led by Mukanna is described. There were other popular liberation movements. This shows that the spread of Islam has passed a long and thorny path. Islam is the dominant religion in Uzbekistan today.Keywords: Arab conquest, Caliphate, monotheistic religion, Prophet Muhammad, Maverannahr
Keywords: Arab conquest; Caliphate; Monotheistic Religion; Prophet Muhammad; Maverannahr